Implementing Risk Management to Enhance Navigation Safety in Indonesian Maritime Domain - Rosnani; Euis Happy Wangloan; I Kadek Laju; Rizal Rochmansyah (Bulletin of Pedagogical Research, 2025)
This study examines the implementation of risk management to improve maritime safety at Teluk Bayur Port, aiming to (1) analyze risk management practices and (2) identify principal risk factors. A descriptive case-study design with supporting quantitative analysis was applied; data were collected by field observation, questionnaires (n = 90, purposive sampling) and documentation; analyses included descriptive percentages, simple regression, SWOT and risk assessment. Results show high awareness of risk management (87.7%) but a significant training gap (53.8% never trained). The main risk factor is adverse weather (82.7%), followed by inadequate infrastructure and human error. Quantitative analysis indicates a positive and significant effect of risk management implementation on maritime safety (regression coefficient b = 0.432; r = 0.860; R² = 0.739; p = 0.000), meaning 73.9% of safety variance is explained by implementation. Mitigation measures involve digital integration, training, and emergency procedures. Conclusion: risk management at Teluk Bayur is underway but not fully optimal or integrated; recommendations include regular training and simulations, infrastructure and navigation equipment modernization, strengthened inter-agency coordination, and data-driven risk management to shift from reactive to predictive and preventive safety practices.